Déficit de atención en el aprendizaje en niños de la Institución Educativa Estatal Inicial N° 377 Señor de los Milagros Santa Fe, Requena 2021 - Melendez Payahua, Ruth Laly (2023)
The objective of the research was to describe the level of attention deficit in learning in children of the Initial State Educational Institution No. 377 Señor de los Milagros de Santa Fe in Requena during 2022, and finally the findings found after data collection and statistical application. For the methodological part, the descriptive type was considered, and the univariate, field, and crosssectional study design was adopted. As a population and sample, all the children of the educational institution were taken, who were 52. To collect the data, the observation technique was applied through a questionnaire previously validated by experts. The conclusion is that the level of attention deficit of the children of the educational institution Señor de los Milagros of the province of Requena, is high in 44.2% (n=23) average in 42.3% (n= 22) and low only in 13.5% (n=7). In general, the findings show that it is necessary to establish strategies to improve the attention deficit in the child's learning, especially in the four years since it is high in 88.2% (15) of them.